2014
DOI: 10.3389/fnins.2014.00248
|View full text |Cite
|
Sign up to set email alerts
|

Speed accuracy trade-off under response deadlines

Abstract: Perceptual decision making has been successfully modeled as a process of evidence accumulation up to a threshold. In order to maximize the rewards earned for correct responses in tasks with response deadlines, participants should collapse decision thresholds dynamically during each trial so that a decision is reached before the deadline. This strategy ensures on-time responding, though at the cost of reduced accuracy, since slower decisions are based on lower thresholds and less net evidence later in a trial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
4
21
1
Order By: Relevance
“…This optimal urgency signal required a fast transition from a flat early portion to a steep deflection toward the decision bound closer to the deadline (cf. refs 20, 30) that is qualitatively very different from the gradual, approximately linear urgency signals that subjects in the current study appeared to implement. As such, although our subjects responded to deadline-induced speed pressure by adjusting their decision policies in a time-dependent fashion, they failed to do so optimally.…”
Section: Resultscontrasting
confidence: 77%
See 3 more Smart Citations
“…This optimal urgency signal required a fast transition from a flat early portion to a steep deflection toward the decision bound closer to the deadline (cf. refs 20, 30) that is qualitatively very different from the gradual, approximately linear urgency signals that subjects in the current study appeared to implement. As such, although our subjects responded to deadline-induced speed pressure by adjusting their decision policies in a time-dependent fashion, they failed to do so optimally.…”
Section: Resultscontrasting
confidence: 77%
“…Theoretical considerations suggest that such a time-invariant policy is sub-optimal if the potential cost of continued evidence accumulation grows with elapsed decision time, as is often the case in decision-making contexts that place a premium on fast responding1820. Yet, in support of the principle of time-invariance, recent reports have suggested that human decision-makers may fail to implement a dynamic, time-variant commitment policy that would yield higher reward rates in such settings152930. In the present study, we describe strong, convergent evidence to the contrary.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Therefore, we do not claim that our model is better supported than urgency models, either here or in general. However, since a number of studies evaluating the concept of an urgency signal have been unable to support it, suggesting instead that standard sequential sampling models can fully account for all behavioral data (Balci et al, 2011; Karşılar et al, 2014; Hawkins et al, 2015a,b), we propose that forced-excursion model variants should at least be considered as an appropriate alternative to urgency signals, reconciling decades of model-based support for decision boundary variation with recent neural evidence.…”
Section: Discussionmentioning
confidence: 93%